Concepts and Principles of Gene Therapy - Suthamnatpong, Naowarat; Ponpornpisit, Aranya (Journal of Mahanakorn Veterinary Medicine, 2024)
The concept of gene therapy has been around for over a hundred years. However, the research and development for proving the efficacy and safety of gene therapy is tremendously time-consuming and requires huge investments. Moreover, application of gene therapy depends on management techniques of genetic materials which has advanced rapidly just recently. The history of clinical trials on gene therapy from the past to the present reveals both successes and failures. Correspondingly, a clinical trial on gene therapy has to be approved by scientific review and an ethics committee to check that the benefits outweigh the risk. At present, there are several approved gene therapy products for treatment of some diseases, while many products are currently undergoing late phase of clinical trials or waiting for approval. The development of gene therapy is adapted accordingly to the innovations such as CRISPR/Cas9 gene editing that enables the utilization and modernization of gene therapy. In this review, we describe about concepts and principles of gene therapy, namely, the definition, key events in the history of gene therapy, therapeutic indications, type of gene therapy, strategy of gene therapy, ex vivo and in vivo gene therapy, delivery systems, immune responses and adverse drug reactions, and lastly we address some concerns about ethical issues.